Placement on COVID-19 Units Does Not Increase Seroconversion Rate of Pediatric Graduate Medical Residents - Crisci, Timothy; Arregui, Samuel; Canas, Jorge; Hooks, Jenaya; Chan, Melvin; Powers, Cory; Schwaderer, Andrew L.; Hains, David S.; Starr, Michelle C. (Frontiers in Pediatrics, 2021)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated disease COVID-19 (coronavirus disease 2019) has presented graduate medical education (GME) training programs with a unique set of challenges. One of the most pressing is how should hospital systems that rely on graduate medical residents provide appropriate care for patients while protecting trainees. This question is of particular concern as healthcare workers are at high risk of SARS-CoV-2 exposure. Objective: This cross-sectional study sought to assess the impact of hospital COVID-19 patient placement on pediatric graduate medical residents by comparing rates of SARS-CoV-2 seroconversion rates of residents who worked on designated COVID-19 teams and those who did not. Methods: Forty-four pediatric and medicine–pediatric residents at Riley Children's Hospital (Indianapolis, IN) were tested for SARS-CoV-2 immunoglobulin M (IgM) and IgG seroconversion in May 2020 using enzyme-linked immunosorbent assays (Abnova catalog no. KA5826), 2 months after the first known COVID-19 case in Indiana. These residents were divided into two groups: those residents who worked on designated COVID-19 teams, and those who did not. Groups were compared using χ2 or Fisher exact test for categorical variables, and continuous variables were compared using Student t testing. Results: Forty-four of 104 eligible residents participated in this study. Despite high rates of seroconversion, there was no difference in the risk of SARS-CoV-2 seroconversion between residents who worked on designated COVID-19 teams (26% or 8/31) and those who did not (31% or 4/13). Eleven of 44 residents (25%) tested positive for SARS-CoV-2 IgG, whereas only 5/44 (11.4%) tested positive for SARS-CoV-2 IgM, without a detectable difference between exposure groups. Conclusion: We did not observe a difference in SARS-CoV-2 seroconversion between different exposure groups. These data are consistent with growing evidence supporting the efficacy of personal protective equipment. Further population-based research on the role of children in transmitting the SARS-CoV-2 virus is needed to allow for a more evidence-based approach toward managing the COVID-19 pandemic.